Life-cycle risk-taking with personal disaster risk - Fabio C. Bagliano; Carolina Fugazza; Giovanna Nicodano (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2021)
This paper examines households' self-insurance in financial markets when a rare personal disaster, such as disability or long-term unemployment, may occur during working years. Personal disaster risk alters lifetime ex-ante investment choices, even if most workers will not experience a disaster. Uncertainty about the size of human capital losses, which characterizes rare disasters, results in lower risk-taking at the beginning of working life, and is crucial in order to match the observed age profiles of US investors from 1992 to 2016.
Keywords: D15; E21; G11; 330; disaster risk; portfolio choice; non-linear income process; unemployment risk; disability risk; beta distribution